Answer: 16a + 32b - 8c
Step-by-step explanation:
8(2a + 4b - c ) = 16a + 32b - 8c
Multiply 8 by 2a to get 16a
Multiply 8 by 4b to get 32b
Multiply 8 by -c or -1c to get -8c
Put them together to get 16a + 32b - 8c
Step-by-step explanation:
Lets first find the remainder when p(x) is divided by x-2
p(2)=2(2)³+b(2)²+3(2)-5
p(2)=16+4b+6-5
p(2)=4b+17
Now let's find the remainder when q(x) is divided by x-2
q(2)=(2)³+(2)²-4(2)-b
q(2)=8+4-8-b
q(2)=4-b
Now let's equate both of them
4b+17=4-b
4b+b=4-17
5b=-13
b=-13/5 as required
Answer:
Step-by-step explanation:
<h3>Given</h3>
- h(x) = (f ο g)(x)
- h(x) =
![\sqrt{x+5}](https://tex.z-dn.net/?f=%5Csqrt%7Bx%2B5%7D)
- f(x) =
![\sqrt{x+2}](https://tex.z-dn.net/?f=%5Csqrt%7Bx%2B2%7D)
<h3>To find</h3>
<h3>Solution</h3>
<u>We know that:</u>
<u>Substitute x with g(x) and solve for g(x):</u>
= ![\sqrt{g(x)+2}](https://tex.z-dn.net/?f=%5Csqrt%7Bg%28x%29%2B2%7D)
- x + 5 = g(x) + 2
- x + 3 = g(x)
- g(x) = x + 3
Answer:
y = 1/2x - 7
Step-by-step explanation:
slope intercept form:
y = mx + b
y = -5
m(slope) = 1/2
x = 4
y = mx + b
<em>substitute </em>
-5 = 1/2*4 + b
-5 = 2 + b
-5 - 2 = b
-7 = b
y = 1/2x - 7